Design and 3D printing of a stainless steel reactor for continuous difluoromethylations using fluoroform. Issue 6 (15th November 2017) - Gutmann, Bernhard; Köckinger, Manuel; Glotz, Gabriel; Ciaglia, Tania; Slama, Eyke; Zadravec, Matej; Pfanner, Stefan; Maier, Manuel C.; Gruber-Wölfler, Heidrun; Oliver Kappe, C.
Abstract : The design and 3D printing of a stainless steel reactor for reaction with a gaseous reagent is described. Abstract : Herein we present a continuous flow reactor printed from stainless steel by selective laser melting. The reactor was specifically designed for a fast difluoromethylation reaction with n BuLi as base and fluoroform as atom-economic and inexpensive reagent. The reactor features four inlets to allow introduction of substrate, n BuLi, fluoroform, and a final quench solution. The reaction was completed within less than 2 min at −65 °C. The utilization of stainless steel as reactor material is critical to accomplish the heat transfer as well as the chemical and mechanical resistance that is required for this transformation.